Implikasi Perubahan Kurikulum Pendidikan Nasional Terhadap Kualitas Pembelajaran Dan Prestasi Siswa - Salsabila Azahra (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
The curriculum has a major influence on the quality of education in a country. The Indonesian curriculum has changed over time to adapt to the times and needs of society. Qualitative descriptive methods and library approaches are used in this study to find out how changes in the national educational curriculum affect the quality of learning and student performance. On the positive side, students will have a better ability to adapt to the developments of the times, improving the quality of education in schools. On the negative side, students may experience a decrease in performance because they are unable to adjust to the new learning system, and educators or teachers should also reconsider the established curriculum.